Leptin in nonalcoholic fatty liver disease - (:unkn) unknown (ELSEVIER ESPANA, 2008)
Background: Non-alcoholic fatty liver disease (NAFLD) is a prevalent condition associated with obesity and insulin resistance (IR). Leptin plays a key role in the control of energy balance, and insulin sensitivity. In this study, we aimed to examine whether serum leptin levels correlate with insulin resistance, oxidative stress parameters and the severity of histological changes in NAFLD. Methods: Fifty-two patients (M/F: 28/24) with no alcohol intake and biopsy-proven diagnosis of NAFLD were studied. Serum leptin levels were measured by radioimmunoassay. HOMA (homeostasis model assessment) IR index was calculated. Comparisons between the patients with NAFLD and non-alcoholic steatohepatitis (NASH) were performed using the Student's t test. N-fultivariate regression analysis and the area under the receiver operating characteristic (ROC) curve were used to identify the independent predictors for NASH. Results: We found no association between serum leptin, fasting insulin levels, and oxidative stress parameters. ROC curve and multiple regression analysis revealed no association between the severity of histological changes and serum leptin levels. During six months followed-up period only NASH group with elevated leptin levels had significant reductions of ALT and AST values (p = 0.03, and 0.005, respectively). Conclusion: Our findings show a preventive effect of leptin against progressive liver injury in NAFLD.
Keywords: Non-alcoholic fatty liver disease; leptin; reactive oxygen species; insulin resistance; NECROSIS-FACTOR-ALPHA; COLLAGEN PRODUCTION; STELLATE CELLS; SERUM LEPTIN; RECEPTOR; STEATOHEPATITIS; FIBROSIS; OBESITY; IDENTIFICATION; STEATOSIS